Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2024)
Table of Content:1. Vulnerability to the climate cycle and Assessing its effects on vegetation in Saudi Arabia A Case Study of the Prince's Reserve Mohammed bin Salman ReserveMr. Abdulla Ahmed Alabdali2. The general situation of COVID-19 in IraqAsst-Prof. Eman Mohammed Hussain, Asst-Prof. Hussein Kamil Awad, Asst-Prof. Emam Atiyah Ibadi3. Comparison of the production performance of some phenotypic groups and their crosses  of quail birdsAsst-Prof. Esraa Mobasher Tawfeq
Keywords: Journal of Agricultural, Environmental and Veterinary Sciences